DEVIATION AND PARALLELISM IN LONGFELLOW’S THE RAINY DAY: A STYLISTIC STUDY - Ameen , Wirya; Ahmed, Mohammed (Humanities Journal of University of Zakho, 2025)
The present paper is an attempt to analyze Longfellow’s ‘The Rainy Day’ (1842) from the perspective of parallelism and deviation which are two stylistic tools utilized to unravel the intention behind any given literary work. These stylistic devices are said to have been utilized by writers as strategies to establish a hierarchy of meanings and themes in the text, bringing some to the fore, shifting others to the background, or repeating some structural features here and there. The procedure adopted is analyzing the poem under study, which consists of three stanzas, in the light of the above mentioned stylistic devices, highlighting their role in revealing the poet’s intention behind this literary work. The paper has come out with certain conclusions, such as that the poet utilizes parallelism to convey the cyclic repetition of natural and social events which often cause boredom and monotony; internal deviation is utilized by the writer to result in a contrast between an idea expressed in the first two stanzas, and another stated in the third. The paper rounds off with a list of the references from which inspirations have been taken.